Laporan Kasus : Prolaps Kloaka pada Kura Sulcata (Geochelone sulcata) - Fauzan, Hazrori (VITEK : Bidang Kedokteran Hewan, 2023)
Cloacal prolapse is a protrusion of the tissues in the cloaca out of the body, so that the mucosa of the cloaca is visible. Cloacal prolapse in turtles can be caused by faecal impaction caused by ingestion of foreign bodies such as sand, bark, or gravel, dystocia, intestinal parasitism, cloacalith, uroliths, neoplasia, space-occupying lesions in the coelomic cavity and foreign body damage. A sulcata tortoise named Kardun is 2 years old, weight 1.17 kg, with complaints of weakness, prolapse from yesterday, does not want to eat and drink, feeds are often given hibiscus and cactus, type of outdor treatment and there are urates discharge. The diagnosis is based on the results of X-ray examination and blood tests. Before the operation, the sulcata tortoise was injected with local anesthesia using lidocine 0.11 ml, a dose of 0.11 mg/kg and after the operation, an injection of the antibiotic Enrofloxacin 0.07 ml, a dose of 5-10 mg/kg, Dexamethasone 0.05 ml, a dose of 2-4 mg/kg, Multivitamin Vigantol® 0.1 ml dose 0.06-0.1 mg/kg.